The benefits of cholinergic enhancement during perceptual learning are long-lasting - Rokem, Ariel; Silver, Michael A. (Frontiers in Computational Neuroscience, 2013)
The neurotransmitter acetylcholine (ACh) regulates many aspects of cognition, including attention and memory. Previous research in animal models has shown that plasticity in sensory systems often depends on the behavioral relevance of a stimulus and/or task. However, experimentally increasing ACh release in the cortex can result in experience-dependent plasticity, even in the absence of behavioral relevance. In humans, the pharmacological enhancement of ACh transmission by administration of the cholinesterase inhibitor donepezil during performance of a perceptual task increases the magnitude of perceptual learning (PL) and its specificity to physical parameters of the stimuli used for training. Behavioral effects of PL have previously been shown to persist for many months. In the present study, we tested whether enhancement of PL by donepezil is also long-lasting. Healthy human subjects were trained on a motion direction discrimination task during cholinergic enhancement, and follow-up testing was performed 5-15 months after the end of training and without additional drug administration. Increases in performance associated with training under donepezil were evident in follow-up retesting, indicating that cholinergic enhancement has beneficial long-term effects on PL. These findings suggest that cholinergic enhancement of training procedures used to treat clinical disorders should improve long-term outcomes of these procedures.